Crystallization of colourless hexanitratoneptunate(iv) with anhydrous H+ countercations trapped in a hydrogen bonded polymer with diamide linkers. Issue 10 (7th February 2020) - Takao, Koichiro; März, Juliane; Matsuoka, Moe; Mashita, Takanori; Kazama, Hiroyuki; Tsushima, Satoru
Abstract : Centrosymmetric hexanitratoneptunate(iv ) crystallizes with anhydrous proton countercations trapped in a hydrogen bonded polymer with diamide linker molecules to give colourless crystals. Abstract : Colourless crystalline compounds of centrosymmetric [Np(NO3 )6 ] 2− were yielded from 3 M HNO3 aq in the presence of double-headed 2-pyrrolidone derivatives (L ). In the obtained crystal structures, H + was also involved as a countercation to compensate for the negative charge of [Np(NO3 )6 ] 2−, where the initial hydration around H + was fully removed during crystallization despite it having the strongest hydration enthalpy. Instead, this anhydrous H + was captured by L to form a [H + ⋯L ] n hydrogen bonded polymer. In [Np(NO3 )6 ] 2−, the Np 4+ centre is twelve-coordinated with 6 bidentate NO3 −, and therefore, present in an icosahedral geometry bearing inversion centre. In such a centrosymmetric system, any f–f transitions stemming from the 5f 3 electronic configuration of Np 4+ are electric-dipole forbidden. This is the reason why the compounds currently obtained were colourless unlike ordinary Np(iv ) species, which are olive-green.